Wasathiyah dalam Gerakan Muhammadiyah: Praktik Lokal di Pimpinan Daerah Muhammadiyah Lamandau - Dana; Maulidiyah Nishfi Hikmah; Mardiana Dina (Yayasan Madinah Al-Aziziyah, 2026)
This study examines the implementation of wasathiyah (Islamic moderation) within the Muhammadiyah movement at the local level, particularly in Lamandau Regency. This research employs a qualitative descriptive approach based on literature review and institutional practices. The findings indicate that moderation values in Muhammadiyah are not merely conceptual but are manifested in practical forms through Amal Usaha Muhammadiyah (AUM) and autonomous organizations. The existence of SMP Islam At-Tanwir, TPA At-Tanwir, Day Care services managed by ‘Aisyiyah, and activities centered in Masjid At-Tanwir reflects the integration of balance, social adaptation, and community-oriented values. Additionally, the involvement of autonomous organizations such as ‘Aisyiyah, Pemuda Muhammadiyah, Tapak Suci, and LAZISMU strengthens inclusive and transformative Islamic moderation. This study concludes that Muhammadiyah in Lamandau represents a contextual and progressive model of moderate Islam.